SINERGITAS PEMBERDAYAAN PONDOK PESANTREN - Putra, Purnama; Huda, Nurul; Basri, Hasan; Alrasyid, M. Harun; Sardiana, Anna; Amalia, Rizqi Maulida; -, Puspita; -, Zulfison; Amalia, Alvien Nur; Qurnain, Dewi Savitri (DEVOSI, 2020)
The existence of pesantren in the midst of society has a very strategic meaning. Pesantren institutions that are rooted in the community, especially rural communities, are a separate force in arousing the enthusiasm and passion of the community for progress. One of the pesantren that has a long history of the Republic of Indonesia is pesantren Cijati Majalengka. Darul Falah Islamic Boarding School, Cijati. The Community Empowerment Program in Islamic Boarding Schools in terms of economic, social, psychological-counseling, religion, education and other aspects through community service cooperation between universities and partners is expected to provide optimal empowerment for the pesantren environment and the communities around the pesantren area. This service was carried out at the Darul Falah Islamic Boarding School which is located at Jl. K.H Mahfud No. 23 Kelurahan Cijati Kec / Kab. Majalengka with in-house training methods, in the form of socialization, training, and consultation. The conclusion of the community service carried out is the need for a holistic empowerment synergy to increase the potential of the pesantren.